What information do patients recall from the third molar surgical consultation?. Issue 6 (June 2020) - Shakir, F.; Miloro, M.; Ventura, N.; Kolokythas, A.
Abstract: The aim of this study was to determine whether the use of a professionally prepared educational video on third molar extraction enhances comprehension and retention of general and informed consent information. A prospective cohort study of adult patients undergoing consultation followed by extraction of third molars in the Oral and Maxillofacial Surgery Clinic, University of Illinois at Chicago was completed. At the initial consultation, the subjects viewed an educational video and received specific verbal individual information about their case. A written examination (group 1) was then completed; a subgroup of the subjects (group 2) was selected randomly to complete the same examination at the next visit prior to the procedure. The primary predictor variable was utilization of the video. The primary outcome variable was comprehension of information regarding third molars, assessed by examination scores. The secondary outcome variable was retention of the information, assessed by repeat examination scores. One hundred adults (34 male, 66 female; group 1) completed the examination at least once; 54 (19 male, 35 female) completed both examinations (group 2). Correct responses ranged from 64% to 100% in group 1 and from 37% to 100% in group 2. In group 2, all questions answered incorrectly at the first visit were answered correctly at the second visit, without any additional information being provided. Patient comprehension and retention of pertinent pre-surgical information is poor, despite use of an educational video to supplement the usual verbal consultation. These results confirm those of prior studies and may have medico-legal implications regarding the informed consent process for third molar surgery.